Analisis Penerapan Sop Dalam Peminjaman Dan Pengembalian Arsip Di Dinas Kependudukan Dan Pencatatan Sipil Kota Tanjungpinang - Siti Hidayah; Nazaki .; Nur Aslamaturrahmah Dwi Putri (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
This study aims to analyze the application of Standard Operating Procedures (SOP) in the process of borrowing and returning archives at the Tanjungpinang City Population and Civil Registration Office. Archives have an important role in supporting the smooth administration and public services so that it is necessary to manage archives in an orderly, effective manner, and in accordance with applicable procedures. However, in its implementation, various obstacles are still found such as records that are still not well organized, delays in the process of returning archives, and weak supervision of borrowed archives, which affect the effectiveness of the implementation of SOPs in archive management. This study uses a descriptive qualitative research method with data collection techniques through observation, interviews, documentation, and dissemination of pre-research questionnaires to staff who routinely borrow archives. The informants in this study amounted to 7 staff involved in the process of borrowing and returning archives. The pre-research results showed that 72% of respondents stated that the implementation of SOPs was still not running optimally, while 28% of respondents stated that SOPs had run well. The results of the study show that the implementation of SOPs in borrowing and returning archives at the Tanjungpinang City Disdukcapil actually has clear procedures, ranging from recording loans, return deadlines, to archive supervision. However, the implementation is still not optimal because there are several obstacles such as manual archival recording, delay in returning archives, incomplete recording of loans, limited facilities and infrastructure, and lack of supervision of borrowed archives. In addition, the limitation of human resources (HR) in the field of archives also affects the effectiveness of the implementation of SOPs. Efforts that can be made to overcome these obstacles are through the implementation of an archive digitization system, improving the quality of human resources through socialization and training, increasing supervision of archives, and adding archival support facilities. With these improvements, it is hoped that the implementation of SOPs in borrowing and returning archives at the Tanjungpinang City Disdukcapil can run more effectively, orderly, and be able to improve the quality of administrative services to the community.